Land Surface Temperature (LST) Distribution Across Ogbaru Local Government Area of Anambra State - Iguocha Arinze Christian (Research in Science and Mathematics Education, 2025)
Purpose – Land Surface Temperature (LST) is a key parameter in understanding the thermal dynamics of any given area, serving as an important indicator for assessing urban heat islands, climate change, and land use patterns. This study investigates the distribution of LST across Ogbaru Local Government Area (LGA) of Anambra State, Nigeria, utilizing remote sensing technology and Geographic Information System (GIS) to assess spatial and temporal trends between 1986 and 2020. The research utilizes secondary data, including LANDSAT imagery from 1980, 2000, and 2020, shapefiles, and Google Earth maps for visual interpretation. Method - Data was further validated through field surveys using GPS and ground-truthing methods. The study also used LANDSAT’s Thematic Mapper (TM), Enhanced Thematic Mapper Plus (ETM+), and Operational Land Imager (OLI) for LST estimation Pearson’s Product Moment Correlation was applied to analyze the relationship between land use/cover and LST across the region. Results - The results reveal a significant rise in LST over the study period, with temperatures in 1986 ranging from 19.4°C to 33.3°C, increasing to temperatures between 22.3°C and 38.7°C by 2002, and reaching 24.4°C to 34°C by 2020. The increase in those temperatures was primarily attributed to urbanization, land use changes, and the expansion of impervious surfaces, particularly in the northern and urbanized parts of Ogbaru, including the proximity to Onitsha. The study also highlights the regional disparity in LST, with higher temperatures in built-up areas and lower temperatures in vegetated zones. Findings -These trends emphasize the growing influence of urban development on local temperature variations and underline the importance of sustainable land use planning and climate adaptation strategies to mitigate the effects of urban heat islands in Ogbaru LGA and similar areas.